Pesan Kebangsaan Gus Muwafiq di Media Sosial Youtube - Tisa, Afiantara Putraning; Wijaya, Ida Suryani (Dimar Jaya Publishing, 2023)
This research aims to analyze the nationalism message conveyed by Gus Muwafiq in his preaching on the YouTube channel. This research uses media textual analysis methods. The results of this research show that Gus Muwafiq's nationalism message contains: 1). History, namely relating to the phases where the Indonesian nation was a separate kingdom, until it became a unified state, the Republic of Indonesia. 2). Religiousity, Gus Muwafiq's preaching contained the knowledge that this nation was built though Islamic values, even applied to the constitutional level. 3). Love. It is related to the development of a sense of pride in the nation where love of the homeland is the basis for the strength of the nation. 4). Ideology, namely Pancasila as the ideology of the Indonesian nation is the basis of the nation and state.